2016
DOI: 10.2151/sola.2016-009
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Westerly and Easterly Wind Events: Observational Evidence

Abstract: Westerly (WWEs) and easterly (EWEs) wind events, shortlived anomalous westerly and easterly surface winds, are known to occur with unusual large magnitude over the equatorial Pacific. As their relative frequency of occurrence and dependence on background conditions are yet to be fully clarified, we analyzed daily surface winds for 1982−2013 from which WWEs and EWEs are detected. Both types of events appear over the Pacific warm pool, where sea surface temperature (SST) is sufficiently high for active deep conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In reality, the timing and location of WWEs are state dependent, that is, partly controlled by background SST, sea level pressure, and low-level zonal wind (Lengaigne et al 2003;Yu et al 2003;Eisenman et al 2005;Seiki and Takayabu 2007a, b;Sooraj et al 2009;Miyama and Hasegawa 2014;Hayashi and Watanabe 2016). Generally, WWEs frequently appear over the western Pacific warm pool, and their timing is partly determined by atmospheric intraseasonal phenomena such as the MJO (Puy et al 2015), although the statistical relationship between the WWEs and MJO is not very significant in previous studies (Seiki and Takayabu 2007a;Chiodi et al 2014).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In reality, the timing and location of WWEs are state dependent, that is, partly controlled by background SST, sea level pressure, and low-level zonal wind (Lengaigne et al 2003;Yu et al 2003;Eisenman et al 2005;Seiki and Takayabu 2007a, b;Sooraj et al 2009;Miyama and Hasegawa 2014;Hayashi and Watanabe 2016). Generally, WWEs frequently appear over the western Pacific warm pool, and their timing is partly determined by atmospheric intraseasonal phenomena such as the MJO (Puy et al 2015), although the statistical relationship between the WWEs and MJO is not very significant in previous studies (Seiki and Takayabu 2007a;Chiodi et al 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Although the ITCZ cannot interact with the warmer SSTA induced by the WWE in cold cases, there is the interaction between them in moderate warm cases, similar to the neutral cases. Because, in nature, the strength of zonal wind is skewed positively over the western equatorial Pacific (e.g., Hayashi and Watanabe 2016), the WWE is a candidate for the phenomena that generate the asymmetry of the ENSO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the eastward counterpart to the WWEs, known as the easterly wind surges (EWSs), were claimed to be important for the onset and development of La Niña (Chiodi and Harrison 2015). Observational evidence shows that the WWEs and EWSs exhibit several asymmetric features, such as zonal extension (Puy et al 2016) and frequency of occurrence (Hayashi and Watanabe 2016). The basic characteristics of WWEs and EWSs and their relationship with ENSO has been extensively studied, although the root causes of these wind bursts are still debated (Chang et al 1979;Keen 1982;Love 1985;Nitta 1989;Lander 1990;Chiodi et al 2014;Puy et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many observational studies in the recent period have shown that the El Niño Modoki has intensified in the past 3 decades (Lee and McPhaden, 2010). Numerous studies (e.g., Weng et al, 2007;Kim et al, 2009;Taschetto and England, 2009;Lee and McPhaden, 2010;Mo, 2010;Yu et al, 2010;Feng et al, 2011;Yu and Kim, 2011;Kim et al, 2012;Yu et al, 2012;Yuan and Yang, 2012;Wang, 2013, 2014;Liu et al, 2014;Capotondi et al, 2015;Hayashi and Watanabe, 2016;Tan et al, 2016) have demonstrated different impacts of these two types of El Niños on many regional phenomena like the summer climate of the Pacific rim countries, East Asian summer climate, Atlantic hurricane frequency, warming in the south Pacific ocean, and winter surface temperature of the United States etc. Using a simple baroclinic model Feng et al (2010) have studied the impacts of conventional ENSO and El Niño Modoki on wintertime Southeast Asian rainfall and related mechanisms.…”
Section: Introductionmentioning
confidence: 99%